Usefulness of Shock Index to Predict Outcomes of Trauma Patient: A Retrospective Cohort Study - Myoung Jun Kim; Jung Yun Park; Mi Kyoung Kim; Jae Gil Lee (Journal of Trauma and Injury)
Purpose We investigated how prehospital, emergency room (ER), and delta shock indices (SI) correlate with outcomes including mortality in patients with polytrauma. Methods We retrospectively reviewed the medical records of 1,275 patients who visited the emergency department from January 2015 to April 2018. A total of 628 patients were enrolled in the study. Patients were divided into survivor and non-survivor groups, and logistic regression analysis was used to investigate independent risk factors for death. Pearson coefficient analysis and chi-square test were used to examine the significant relationship between SI and clinical progression markers. Results Of 628 enrolled patients, 608 survived and 27 died. Multivariate logistic regression analysis reveals “age” (p<0.001; OR, 1.068), “pre-hospital SI >0.9” (p<0.001; OR, 11.629), and “delta SI ≥0.3” (p<0.001; OR, 12.869) as independent risk factors for mortality. Prehospital and ER SIs showed a significant correlation with hospital and intensive care unit length of stay and transfusion amount. Higher prehospital and ER SIs (>0.9) were associated with poor clinical progression. Conclusions SI and delta SI are significant predictors of mortality in patients with polytrauma. Moreover, both prehospital and ER SIs can be used as predictive markers of clinical progression in these patients.